2016
DOI: 10.1121/1.4966625
|View full text |Cite
|
Sign up to set email alerts
|

Using line acceleration to measure false killer whale (Pseudorca crassidens) click and whistle source levels during pelagic longline depredation

Abstract: False killer whales (Pseudorca crassidens) depredate pelagic longlines in offshore Hawaiian waters. On January 28, 2015 a depredation event was recorded 14 m from an integrated GoPro camera, hydrophone, and accelerometer, revealing that false killer whales depredate bait and generate clicks and whistles under good visibility conditions. The act of plucking bait off a hook generated a distinctive 15 Hz line vibration. Two similar line vibrations detected at earlier times permitted the animal's range and thus si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Underwater cameras and, more recently, accelerometer devices, have been used as ways to detect cryptic depredation events but unlike acoustics, usually cover small proportions of gear and can hardly be used to fully quantify the conflict unless extensively deployed (IOTC, 2007;Lyle et al, 2016;Mathias, Thode, Straley, & Folkert, 2009;Richard et al, 2020;Thode et al, 2016). Underwater cameras can also help identify the depredating species.…”
Section: Improving Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Underwater cameras and, more recently, accelerometer devices, have been used as ways to detect cryptic depredation events but unlike acoustics, usually cover small proportions of gear and can hardly be used to fully quantify the conflict unless extensively deployed (IOTC, 2007;Lyle et al, 2016;Mathias, Thode, Straley, & Folkert, 2009;Richard et al, 2020;Thode et al, 2016). Underwater cameras can also help identify the depredating species.…”
Section: Improving Monitoringmentioning
confidence: 99%
“…Electronic monitoring cameras on‐board vessels, which have recently emerged to replace or supplement observers in fisheries (Bicknell, Godley, Sheehan, Votier, & Witt, 2016), can potentially improve the monitoring of depredation by recording partially depredated catches, damaged gear and/or by‐catch of depredating species in data poor fisheries. Acoustic recorders can be effective at detecting, and even quantifying, unseen depredation by odontocetes, as evidenced by studies on sperm whales (Mathias, Thode, Straley, & Andrews, 2013; Thode et al, 2015; Thode, Wild, Mathias, Straley, & Lunsford, 2014) and false killer whales (Hernandez‐Milian et al, 2008; McPherson et al, 2004) depredating on longline catches. Underwater cameras and, more recently, accelerometer devices, have been used as ways to detect cryptic depredation events but unlike acoustics, usually cover small proportions of gear and can hardly be used to fully quantify the conflict unless extensively deployed (IOTC, 2007; Lyle et al, 2016; Mathias, Thode, Straley, & Folkert, 2009; Richard et al, 2020; Thode et al, 2016).…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative rate of depredation of bait vs. catch is unknown and likely varies among fisheries, although small cetaceans are likely to engage in this behavior (Gilman et al, 2007a;Werner et al, 2015). Recent video and acoustic evidence confirmed that false killer whales depredate pelagic longline bait in the daytime using both visual and audio cues (Thode et al, 2016). Garrison (2007) also showed lower bycatch rates of Risso's dolphins in the U.S. East Coast pelagic longline fishery when fish bait was used in place of squid bait.…”
Section: Potential Solutionsmentioning
confidence: 99%
“…Firstly, the issue often results in substantial financial losses to the fishers. The amount of fish or bait odontocetes removed from longlines imposes increased fishing time and displacements to achieve quotas and/or to implement strategies of avoidance ( Peterson et al, 2014 ; Thode et al, 2016 ). Secondly, the amount of depredated fish is often inaccurately assessed or unaccounted when setting catch limits, resulting in biased fish stock assessments ( Peterson et al, 2013 ; Peterson & Hanselman, 2017 ; Hanselman, Pyper & Peterson, 2018 ).…”
Section: Introductionmentioning
confidence: 99%